Numerical modelling of hydraulics and sediment dynamics around mangrove seedlings: Implications for mangrove establishment and reforestation. (5th February 2019) - Le Minor, Marine; Bartzke, Gerhard; Zimmer, Martin; Gillis, Lucy; Helfer, Véronique; Huhn, Katrin
Abstract: Mangroves grow in the coastal and intertidal zones at tropical and subtropical latitudes. It is widely accepted that the establishment, growth and survival of mangrove seedling depend on the environmental conditions such as temperature, tidal regime and hydrodynamics. To date we know that, in cohesionless sediment, the higher the flow velocity the greater the eroded volume and, thus, the stronger the scour around the mangrove seedling which can lead to its uprooting or death. However, how a mangrove seedling (cm-scale) alters the flow pattern and the sediment transport is, to date, still poorly understood. Four suits of numerical experiments were setup with the same mangrove seedling and subjected to flow speeds of 5 cm·s −1, 10 cm·s −1 and 15 cm·s −1 as well as a rarely occurring extreme scenario 50 cm·s −1 . The hydro- and sediment dynamics were simulated using a coupled sediment-hydrodynamic continuum approach: the Finite Volume Method utilizing the software package OpenFOAM. The two phases, silty sediment and water, constitute a mixture. The distribution of the sediment phase in the water phase was estimated with the drift-flux approximation. A natural mangrove seedling ( Rhizophora mucronata ) was digitized employing photogrammetry and discretized into the model domain. This numerical model was validated against experimental observations and is able to capture the main features of the flow and sediment transport around a mangrove seedling. The numerical simulations showed that a downward flow associated to a horseshoe vortex enhances scour in front of the mangrove seedling and a vortex shedding keeps the sediment in suspension or re-suspends the sediment in the rear of the mangrove seedling. Thus, a mangrove seedling has a significant influence on the flow pattern and sediment transport: the higher the flow speed, the less stable the sediment bed. Additionally, these findings could help to better understand how the settlement of mangrove seedlings and sediment dynamics affect mangrove establishment and why the colonization or restoration of tidal flats is successful or not. This paper is an initial study focusing on a single mangrove seedling on a cm-scale. It is anticipated to extend the interactions between several seedlings as well as mangrove roots. With this successfully utilized approach, it will be possible in the future to investigate the impact of several mangrove seedlings forming a matrix on a m-scale on sediment dynamics. So, this work creates the basis to study more complex sediment transport processes such as erosion and sediment trapping in mangrove forests. Graphical abstract: Highlights: Three-dimensional coupled hydro-sediment dynamic model. Quantitative analyses of flow and sediment re-mobilization in vicinity of a seedling. Flow speed controls: (a) size of scouring and seedling stability. (b) Magnitude and turbulences right after and further downstream to seedling. (c) Turbulences control resuspension behaviour or suspended load at sediment bed.